Prototype Data Warehouse Aplikasi eM-Tilang - Abdul Azis; Dias Ayu Budi Utami; Albertus Novian BT (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2018)
The development of information technology today is very advanced. One example of the development of information technology is the implementation of a data warehouse. The data warehouse is a reacting database that can be used for query and analysis, object-oriented, integrated, time-variant, unchanging that is used to help decision makers. The eM-Tilang application system that is managed by the police requires the implementation of a data warehouse in order to improve community control on the highway and reduce traffic violations. the implementation of the data warehouse in the eM-Tilang system certainly requires supporting technologies such as data mining, OLAP (Online Analytical Processing), OLTP (Online Transaction Processing), ETL (Extract Transform Loading) / ELT (Extraxt Loading Transform), especially Cloud Computing IAAS (As A Services infrastructure). The implementation of the data warehouse is expected to assist the police in making informed decisions in order to improve public order on the highway and reduce traffic violations.Keywords : Data Warehouse; eM-Tilang; Prototype; Traffic Ticketing